ANALISIS SWOT SEBAGAI STRATEGI MENINGKATKAN DAYA SAING PADA SMA IT NURUL ‘ILMI KOTA JAMBI - Oktariana Manan; K.A Rahman; Ahmad Nopriansyah; Aminah Chandra Kasih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Schools as an industry operating in the field of educational services are a means of improving the quality of human resources that are able to be competitive. The inability of an educational unit to respond to external opportunities and threats will result in reduced competitiveness or hampered achievement of the educational unit's performance (Rahayu, 2008). This research aims to analyze the effectiveness of the SWOT strategy in increasing the competitiveness of a school. In this context, we use a case study at SMA IT Nurul Ilmi, a top level school located in the city of Jambi, Jambi with a leading vision of creating strong, intelligent and noble people. Research methods include collecting qualitative data through interviews with upper level management, analysis of internal company documents, and surveys of customers or key stakeholders. SWOT analysis shows that SMA IT Nurul 'Ilmi has several strengths that can become the basis for strategies to increase competitiveness, namely the advantages of teachers who are young and energetic, interactions between teachers and students are well and harmoniously established, the reputation of teachers who are friendly and nurturing to children, on average -On average, the teachers who teach have a second degree in accordance with the subjects they teach, and the foundation really supports the school program. Weaknesses found in the form of a lack of a system that regulates digitalization, a complex internal system where sometimes boredom in teaching or educating is experienced by some people, there is still a lack of parental support in the development of children's education. Opportunities include developments in educational goals and parents' expectations, changes in government policy, or the evolving needs of students and guardians. Meanwhile threats can come from increasingly intensive competition, changes in regulations, or changes in trends.